A Review of Islamic Criminal Law Regarding Reverse Burden of Proof in Corruption Crimes - Maisa Faizahra Ramadhani; Noor Azizah (Lambung Mangkurat Law Journal, 2025)
Corruption is a complex problem in Indonesia that hinders law enforcement due to difficulties in proving cases. The principle of reverse burden of proof is applied as an effort to overcome this, requiring defendants to prove the origin of their wealth. This study aims to analyze the Islamic criminal law perspective on the application of the principle of reverse burden of proof in corruption cases in Indonesia. The study employs a normative legal method with a literature review. The findings indicate that while Islamic criminal law generally places the burden of proof on the prosecutor, the application of reverse burden of proof can be justified under certain conditions with strong indications of corruption. This study concludes that the application of the principle of reverse burden of proof in Islamic criminal law is acceptable as long as it does not violate the principles of the defendant's rights and is carried out cautiously based on strong preliminary evidence, thereby balancing the eradication of corruption and the protection of individual rights. This study provides practical recommendations for law enforcement agencies in handling corruption cases with reverse burden of proof.